Pengaruh budaya organisasi terhadap komitmen organisasi melalui motivasi kerja - Khikmatul Jazilah (Jurnal Ilmu Manajemen, 2023)
This study aims to analyze and examine the effect of organizational culture on organizational commitment through work motivation. The type of research is explanatory research using a quantitative approach. The number of samples is 42 employees of the manufacturing company. The data is collected using a questionnaire. The measurement scale used in this study is a Likert scale-data analysis technique using Structural Equation Modeling (SEM) and processed using SmartPLS 4.0 software. This study indicates: that organizational culture has no significant effect on organizational commitment; organizational culture has a positive and significant effect on work motivation; work motivation has a positive and significant effect on organizational commitment. This research has implications for manufacturing companies, especially regarding organizational culture, organizational commitment, and work motivation. Companies must maintain and improve organizational culture and work motivation in the company, thereby creating and influencing the increase in employee organizational commitment.